Resonant wireless power transmission based on resonant electrical coupling - Fernandes, Ricardo Dias (2016)
Contained in this document are theoretical and experimental results related to the feasibility of resonant electrical coupling as a method of wirelessly transferring power across non-negligible distances. As shown, resonant electrical coupling is remarkably similar to resonant magnetic coupling in several aspects. However, while resonant magnetic coupling is currently a method of wirelessly transferring power with a very strong presence in the literature, resonant electrical coupling is not. The lack of material related to resonant electrical coupling, together with the potential of achieving a balanced trade-off between critical features such as efficiency, distance, simplicity, size and power transfer capability, were the main motivations for considering this specific topic. The possibility of constructively combining resonant electrical coupling and resonant magnetic coupling is also addressed. A review of the state of the art of wireless power, not only in terms of scientific publications but also in terms of market adoption and international standards, is included in this document.